A retrospective study on the effects of pulmonary rehabilitation in patients with pulmonary hypertension. (August 2014) - Raskin, Jonathan; Qua, Debbie; Marks, Ted; Sulica, Roxana
A retrospective analysis of 23 patients was undertaken to evaluate the outcome of pulmonary rehabilitation (PR) in patients with pulmonary hypertension (PH) over a preceding 6-year time frame. Chart review and data analyses were undertaken evaluating pulmonary arterial hypertension pharmacotherapy versus the same therapy with the addition of PR. Analysis included 23 patients who had a mean pulmonary artery pressure of 36.6 while on therapy and who had initial six-minute walk tests (6MWTs) ranging between 54 and 396 meters. Outcomes included 6MWTs and Saint George's Respiratory Questionnaire. There was no improvement in 6MWT postpharmacotherapy. Patients with low 6MWT <250 meters had substantial gains in 6MWT postrehabilitation (average of 86 meters). As well, those with initial 6MWT >250 meters had a significant improvement of 52.55 meters, documenting the utility of PR in patients with PH. PH patients are increasingly seen in PR clinics as they share many characteristics present in chronic respiratory disease states. There is increasing literature supporting the utility of PR in this population. We have found that patients with 6MWTs as low as <250 meters are also candidates for PR and can demonstrate substantial benefits as measured using the 6MWTs.